Antibacterial and Microstructure Properties of Titanium Surfaces Modified with Ag-Incorporated Nanotube Arrays - Li,Guangzhong (2016)
Although titanium (Ti) and its alloys have been widely used as implants in clinical settings, failures still occur mainly due to poor bioactivity and implant-associated infections. Here, we coated Ti implants with TiO2 nanotubes (TNTs) incorporated with the antibacterial agent Ag to produce Ag-TNTs, through anodization in AgNO3 and xenon light irradiation. We characterized surface morphology and composition of the coating with scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. We investigated surface topography of the coatings by atomic force microscopy (AFM) operated in the tapping mode. The results indicate that Ag was successfully doped onto the TNTs, and that the nanoparticles were mainly distributed on the surface of TNTs. Finally, our antibacterial experiments reveal that Ag-TNTs on Ti implants exhibit excellent antibacterial activities, which promises to have significant clinical applications as implants.